Variations in some soil physical properties, micronutrient distribution and its stock under high density guava orchard ecosystem - ADAK, TARUN; KUMAR, KAILASH; SINGH, VINOD KUMAR (Journal of Soil and Water Conservation, 2020)
Long term orchard management may impact the soil properties over the period of orchard management. Estimating such variations is essentially important for evolving a strategic/sound nutrient management module. The present investigation was therefore aimed to assess the variations in some soil physical properties, micronutrients and its stock under long-term orchard ecosystem of guava cv. Lalit (555, 277 and 5000 plants ha-1) with spacing of 3×6 m, 6×6 m and 2×1 m. Wide variations in soil properties were observed. Marginal variations in soil bulk density and water holding capacity as affected by different plantations was noted. Porosity of 39.49% was recorded under normal density of 277 plants ha-1 while 42.85 and 40.66 per cent in 555 and 5000 plants ha-1. Mean water holding capacity was estimated as 21.44%. Higher DTPA-extractable micronutrients (Zn, Cu, Mn and Fe) were recorded in more densely populated system than normal density. The Zn stock of 2.28, 2.42 and 5.50 kg ha-1 was estimated under 277, 555 and 5000 plants ha-1. A lower range of Cu stock (4.85 to 6.89 kg ha-1) across systems was found. Similarly, the highest distribution of Mn stock (29.11 kg ha-1) was found in the category 5000 plants ha-1 than 23.98 kg ha-1 in 555 plants ha-1. Fe stock with maximum value of 54.96 kg ha-1 was estimated in the category of 5000 plants ha-1 followed by 39.06 kg ha-1 in 555 plants ha-1 and the lowest was recorded as 30.85 kg ha-1 (normal 277 plants ha-1).